DAMPAK RETRIBUSI DAERAH, PERAN SISTEM INFORMASI AKUNTANSI PADA PENDAPATAN ASLI DAERAH DI ERA PANDEMI COVID-19 - Lesi Hertati; Lilis Puspitawati; Rilla Gantino; Meifida Ilyas (Program Studi Akuntansi Fakultas Ekonomi dan Bisnis Universitas Riau, 2021)
This study aims to examine the effect of regional levies and the use of accounting information systems on Regional Original Income during the Covid 19 pandemic. This research was conducted on the Musi Banyuasin Regional Government using a purposive sampling technique, namely selecting the OPD that collects regional retribution. Respondents in this study were the State Civil Apparatus in the accounting sub-section 23 people and 23 people in informatics. Data was collected by sending questionnaires directly to respondents. Data analysis was performed using Structural Equation Modeling (SEM) with Smart PLS 3.0. The results showed that the regional retribution did not have a significant effect on increasing PAD, but the accounting information system had a significant effect on increasing the local revenue of Musi Banyuasin Regency. The results of this study contribute to the government in increasing PAD can be done by utilizing accounting information systems